Changes in fruit and vegetable consumption habits from pre-pregnancy to early pregnancy among Norwegian women - Marianne Skreden; Elling Bere; Linda R. Sagedal; Ingvild Vistad; Nina C. Øverby (BMC, 2017)
Abstract Background A healthy diet is important for pregnancy outcome and the current and future health of woman and child. The aims of the study were to explore the changes from pre-pregnancy to early pregnancy in consumption of fruits and vegetables (FV), and to describe associations with maternal educational level, body mass index (BMI) and age. Methods Healthy nulliparous women were included in the Norwegian Fit for Delivery (NFFD) trial from September 2009 to February 2013, recruited from eight antenatal clinics in southern Norway. At inclusion, in median gestational week 15 (range 9-20), 575 participants answered a food frequency questionnaire (FFQ) where they reported consumption of FV, both current intake and recollection of pre-pregnancy intake. Data were analysed using a linear mixed model. Results The percentage of women consuming FV daily or more frequently in the following categories increased from pre-pregnancy to early pregnancy: vegetables on sandwiches (13 vs. 17%, p <0.01), other vegetables (11 vs. 14%, p = 0.01), fruits (apples, pears, oranges or bananas) (24 vs. 41%, p < 0.01), other fruits and berries (8 vs. 15%, p < 0.01) and fruits and vegetables as snacks (14 vs. 28%, p < 0.01). The percentage of women who reported at least daily consumption of vegetables with dinner (22% at both time points) was stable. A higher proportion of older women increased their consumption of vegetables and fruits as snacks from pre-pregnancy to early pregnancy compared to younger women (p=0.04). Conclusions We found an increase in the proportion of women consuming FV daily or more frequently from pre-pregnancy to early pregnancy. Trial registration ClinicalTrials.gov database, NCT01001689 . https://clinicaltrials.gov/ct2/show/NCT01001689?term=NCT01001689&rank=1 .